- 198

- 0

**1. Homework Statement**

I'm having a bit of difficulty understanding the unit step function

For example

f(t) = 6u(-t) + 6u(t+1) - 3u(t+2)

t = -1

**2. Homework Equations**

**3. The Attempt at a Solution**

If t = -1 then the way I would do the problem is say that if u(t) returns a negative number or zero then it's zero

6(1) + 6u(0) - 3(1) = 3

However, the answer is 9 so I must be misinterpreting how the unit step function works. Can anyone explain to me how one would handle the unit step function in this situation?